Muslim identity in a turbulent age: Islamic extremism and Western Islamophobia - Hardy, Mike; Mughal, Fiyaz; Markiewicz, Sarah (Jessica Kingsley Publishers, 2017)
Introduction / Mike Hardy, Fiyaz Mughal and Sarah Markiewicz -- The history of the Amman message and the promotion of the Amman message project / Sarah Markiewicz -- Taking the Amman message to European audiences: a message for Muslims and non-Muslims alike / Mike Hardy -- Islam in Europe and the Amman message: overview, challenges and potentials / Rebecca Catto -- Islam in the United Lingdom and the impact of the Amman message / Fiyaz Mughal -- Young British muslims: online extremism and the message of Islam / Imran Awan -- The Amman message: an early confrontation with extremist Islamic movements / Jamal al-Shalabi -- The Amman message: a counter narrative to Islamic fundamentalism / Mohd Khair Eiedat -- The Amman message as an invitation to interfaith dialogue: a Christian response / Christine Seeberg -- Charlie Hebdo and the Amman message: a counter narrative to violent fundamentalism? / Steve Rose & Faith Matters -- The Amman message "other": repositioning identity politics for dialogue and justice / Kristin Shamas -- Looking forward: an impossible road? / Mike Hardy, Fiyaz Mughal and Sarah Markiewicz